Literacy in the new media age - Kress, Gunther R., 1940- (Routledge, Taylor & Francis Group, 2003)
"Kress explores all aspects of the materiality of writing in an integrated social semiotic and multimodal framework. He reveals ways in which new media is changing literacy and looks at how we should think about literacy in the age of the new media."
Keywords: gramotnost; ICT gramotnost; písemná komunikace; digitální média -- sociální aspekty; literacy; ICT literacy; written communication; digital media -- social aspects; studie; studies